ANGULAR DEPENDENCE OF THE SWITCHING FIELD AND IMPLICATIONS FOR GYROMAGNETIC REMANENT MAGNETIZATION IN THREE-AXIS ALTERNATING-FIELD DEMAGNETIZATION - Madsen K.N. (My University, 2004)
The critical field for reversing the magnetic moment of a single-domain (SD) grain, the switching field, is a function of the angle between the field and the grain's easy axis of magnetization. The functional relationship derived for coherent reversal, i.e. spins reversing in unison, differs from that of various incoherent mechanisms and of domain wall movement in multidomain (MD) grains. Due to the angular dependence of the switching field, uniaxial alternating-field (AF) demagnetization is less efficient than AF demagnetization with tumbling of the sample. The difference was determined for synthetic and natural rock samples carrying anhysteretic and rotational remanent magnetizations (ARM and RRM respectively). These types of remanence were chosen to activate dominantly SD grains, and their magnitudes relative to saturation isothermal remanent magnetization (SIRM) are discussed in relation to magnetic grain size. For the samples studied, data indicated that the majority of remanence carriers cannot be associated with the Stoner-Wohlfarth model for coherent reversal. In contrast, incoherent reversal or domain wall movement largely explains the observed lag. Based on the angular dependence of switching field corresponding to these models, the acquisition of gyromagnetic remanent magnetization (GRM) during three-axis demagnetization is discussed. In particular it is shown theoretically that the method of Dankers and Zijderveld fails to eliminate completely the effect of GRM in three-axis demagnetization.
Keywords: ALTERNATING FIELD DEMAGNETIZATION; ANGULAR DEPENDENCE; ARM/SIRM RATIO; GYROMAGNETIC REMANENCE; SINGLE-DOMAIN GRAIN; SWITCHING FIELD